'They're Coming': Precarity and the white nation fantasy among South African migrants in Melbourne - McKenzie, H; Gressier, C (SAGE Publications, 2016)
This paper explores the social reproduction of precarity among white South African migrants in Australia. Building on Griffiths and Prozesky’s elucidation of the white South African imaginary and its role in triggering emigration, we draw on ethnographic data on white South Africans living in Melbourne to argue that our informants reproduce what Hage terms a ‘white nation fantasy’. In documenting the ways our informants’ migration experiences can be read as a function of a threatened social imaginary, we suggest that their ‘successful’ resettlement in Australia points to the congruence of their ontological grounding with the white nation fantasy predominating in Australia. Ultimately, however, we argue that the sense of precarity our informants experience in Australia is intrinsically embedded in their reproduction of the white nation fantasy. Our case study therefore serves as a cautionary tale to inflexible constructions of whiteness globally.